Chemometrics unraveling nutrient dynamics during soybean seed germination - Romeu, Sara Luiza Zachi; Marques, João Paulo Rodrigues; Montanha, Gabriel Sgarbiero; de Carvalho, Hudson Wallace Pereira; Pereira, Fabíola Manhas Verbi [UNESP] (Elsevier, 2021)
Laboratory microprobe X-ray fluorescence (μ-XRF) spectrometry is a powerful analytical technique able to detect trace elements in biological samples. The present study compared univariate and multivariate strategies to investigate the elements detected with μ-XRF during soybean (Glycine max (L.) Merrill) germination. The conventional approach, i.e., univariate, showed that the studied micronutrients (Mn, Fe, and Zn) were located mainly on the radicle tip, while the macronutrients (P, S, K, and Ca) were spread through the seed. The score maps, as well the correlation maps from a covariance matrix, were able to evaluate variations of chemical elements, such as P, S, K, Ca, Fe, Mn, Zn, and Rh-scattering effects through the embryo, leading the first glance at elemental distribution and remobilization during soybean seed germination.
Keywords: Chemometrics; Environmental; Germination; Seeds; Soybean; XRF